Marketing Aspects of Social Media Absorption in the Clothing Industry in the Light of Own Research - SuÅ‚kowskiÅukasz (Information Management and Business Review, 2015)
The process of exchange has been an integral part of life since the dawn of civilization, which means that marketing understood in a wide context as a contact between a seller and a market i.e. someone that is willing to buy something â€“ is exactly as old as a notion of exchange (Otto, 2004). Subsequent stages in the process of its evolution have lead to its atomization and a need for exploration of optimal tools and working methods. The era of IT technology and related dynamic development of mobile devices and applications have contributed to an extensive development of social media that to an increasingly greater extent determine marketing activity of contemporary enterprises. Clothing industry is present virtually in every country and it is one of the most important sectors of the global economy. In case of some regions, both in a global and national perspective, it can be a factor that determines their development and further directions of evolution. The ÅÃ³dÅº region that is the subject of the discussion presented below is a perfect example of that trend. The aim of the article is to identify the most popular methods and tools of social media marketing used by the main clothing enterprises from the ÅÃ³dÅº region while taking into account indications for their further diffusion.